2010
DOI: 10.2527/jas.2010-2939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic-, bacteriophage-, or organic acid-supplemented feeds or fermented soybean meal on the growth performance, acute-phase response, and bacterial shedding of grower pigs challenged with Salmonella enterica serotype Typhimurium1

Abstract: A 28-d experiment evaluated the growth performance, acute-phase response, and bacterial shedding patterns in pigs (n = 108; initially, 38.7 ± 6.7 kg) fed 6 treatment diets, including a control diet with no antimicrobial agents (CON), a positive control diet containing chlortetracycline, 100 mg/kg (CT), a diet containing anti-Salmonella Typhimurium bacteriophage, 3 × 10(9) plaque-forming units/kg of feed (ASB), Lactobacillus plantarum CJLP56, 6.5 × 10(8) cfu/kg of feed (LP), 0.2% microencapsulated organic acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
45
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 24 publications
12
45
2
3
Order By: Relevance
“…Our results also corroborate those of Gebru et al (2010). Specifically, we observed that including a blend of microencapsulated organic and inorganic acids in the diet had an effect on Salmonella that was similar to that of chlortetracycline in the control 6 and 14 days after contamination.…”
Section: Resultssupporting
confidence: 81%
“…Our results also corroborate those of Gebru et al (2010). Specifically, we observed that including a blend of microencapsulated organic and inorganic acids in the diet had an effect on Salmonella that was similar to that of chlortetracycline in the control 6 and 14 days after contamination.…”
Section: Resultssupporting
confidence: 81%
“…Our study found that probiotics improved ADG and ADFI and significantly decreased F/G (P < 0.05) in finishing pigs. Similar findings have been reported in studies when probiotics were given to piglets (Choi et al, 2011) and growing-finishing pigs (Gebru et al, 2010;Meng et al, 2010). There are also reports that probiotics have no positive effects on ADG and feed conversion of pigs (Kornegay and Risley, 1996;Estienne and Hartsock, 2005); this may be caused by different probiotic strains used in the experiments.…”
Section: Discussionsupporting
confidence: 81%
“…This shows that bacteriophage is a better feed additive compared with its counterparts; moreover, piglets supplemented with BA also showed improved performance compared to the control group. The positive effects of BA in the current study are in line with previous studies where supplementation with BA in single (Gebru et al 2010) or cocktail ) form improved ADG in pigs. An increase in growth rate could be attributed to the reduction of pathogenic bacteria such as E. coli and Clostridium spp.…”
Section: Discussionsupporting
confidence: 81%
“…Among various non-antibiotic alternatives, OA (Lambert and Stratford 1999;Suryanarayana et al 2012) and zinc sources (Hollis et al 2005) have been used previously. Further, BA have received increasing attention due to their natural antimicrobial properties and the lower propensity for the development of bacterial resistance (Gebru et al 2010;Wittebole et al 2014). The transient period in which weaning pigs progress from lactation to a solid diet is critical and often results in smallintestinal atrophy and dysfunction in piglets (Wu et al 1996).…”
Section: Discussionmentioning
confidence: 99%